Workshop on Increasing the Efficiency and Effectiveness of Hospital Management by Calculating Unit Costs Based on Risk Management - Budhi Setianto; Agus Aan Adriansyah; Akas Yekti Pulih Asih; Yauwan Tobing Lukiyono (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
In running a hospital business in the Era of National Health Insurance (JKN), efficient and effective business management efforts are required, the BPJS tariff application pattern which uses the INA CBGS Tariff requires a form of quality control and cost control, the aim of this community service is to increase knowledge of management procedures. a more efficient and effective hospital based on Risk Management, the method used is to hold a workshop for 64 structural officials of RS X Surabaya to further improve services based on risk management which are managed effectively and efficiently. The workshops provided include material presentations and case studies. The modules provided at the workshop were improving effective and efficient management, Unit Cost and Risk Management, all participants were actively involved in the workshop activities. This workshop provides an additional increase in knowledge which is shown by an increase in the Pretest and Posttest scores with an increase of 25.3% from 62.9, while the Post Test has a mean value of 87.8 from the results of the significance value (2-tailed) in the table. Significance value (2- tailed) of example case this is 0.000 (p < 0.05). So that final Pre Test and Post Test results experience significant change (meaning). Based on statistics descriptive test start and test end proven by final test more tall. Can concluded Workshops increasing the efficiency and effectiveness of hospital management by calculating Unit Cost based on risk management increase knowledge participant.